Nematicidal effect of an Argentine strain of Photorhabdus laumondi laumondi (Enterobacteriaceae) on the free-living nematode Panagrellus redivivus (Rhabditidae: Panagrolaimidae) - Salas, Augusto; Achinelly, María Fernanda; Sauka, Diego Hernan (Elsevier, 2021)
Bacteria with nematicidal effects have attracted interest as biocontrol agents of pests and diseases due to their relatively low environmental impact compared to chemical management strategies1. The damage they cause to target nematodes is diverse and imperfectly understood. Photorhabdus spp. (Enterobacteriaceae) lives symbiotically within the nematode Heterorhabditis spp. (Rhabditida: Heterorhabditidae). It is known that secondary metabolites of this gram-negative bacterium exhibit insecticidal activity, mainly in Lepidopteran and Coleopteran insects. Studies have also shown that cell-free culture filtrates of Photorhabdus spp. have nematicidal activity on free-living nematodes and pest phytonematodes; however, the causes of death in these targets are still being studied.